SDI-118, a novel procognitive SV2A modulator: First-in-human randomized controlled trial including PET/fMRI assessment of target engagement - Botermans, Wouter; Koole, Michel; Van Laere, Koen; Savidge, Jonathan R.; Kemp, John A.; Sunaert, Stefan; Duffy, Maeve M.; Ramael, Steven; Cesura, Andrea M.; D’Ostilio, Kevin; Gossen, Denis; Madsen, Torsten M.; et al. (Frontiers in Pharmacology, 2023)
BACKGROUND: Current treatments for progressive neurodegenerative disorders characterized by cognitive impairment either have limited efficacy or are lacking altogether. SDI-118 is a small molecule which modulates the activity of synaptic vesicle glycoprotein 2A (SV2A) in the brain and shows cognitive enhancing effects in a range of animal models of cognitive deficit. METHODS: This first-in-human study evaluated safety, tolerability, and pharmacokinetics/pharmacodynamics of SDI-118 in single ascending oral doses up to 80 mg administered to 32 healthy male subjects. Brain target occupancy was measured in 8 subjects using positron emission tomography (PET) with PET-ligand [11C]-UCB-J. Food effect was assessed in 7 subjects. Mood state was regularly evaluated using standardized questionnaires, and resting state fMRI data were analyzed as exploratory objectives. KEY RESULTS: At all doses tested, SDI-118 was well tolerated and appeared safe. Adverse events were mainly dizziness, hypersomnia, and somnolence. All were mild in intensity and increased in frequency with increasing administered dose. No dose-limiting adverse reactions were observed at any dose. SDI-118 displayed a linear pharmacokinetic profile with no significant food effect. Brain penetration and target engagement were demonstrated by a dose-proportional SV2A occupancy. CONCLUSION: Single oral doses of SDI-118 up to 80 mg were very well tolerated in healthy male subjects. Dose-proportional SV2A occupancy in the brain was demonstrated with brain imaging. Adverse effects in humans mainly occurred in higher dose ranges, with high occupancy levels, and were all mild and self-limiting. These data support further clinical exploration of the compound in patients with cognitive disorders.